2016
DOI: 10.1111/pace.12836
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Versus Unipolar Temporary Epicardial Ventricular Pacing Leads Use in Congenital Heart Disease: A Prospective Randomized Controlled Study

Abstract: Our study shows that the bipolar leads (Medtronic 6495, Medtronic Inc., Minneapolis, MN, USA) have superior sensing and pacing thresholds in the ventricular position in patients undergoing surgery for congenital heart disease when compared to the unipolar leads (Medical Concepts Europe VF608ABB, Medical Concepts Europe Inc., Buffalo, NY, USA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…We advanced the guide-wire into the area of the old myocardial infarction for pace-mapping; therefore, the pacing threshold at the area was high. Previous reports showed that unipolar pacing threshold was lower compared with the bipolar pacing threshold [10], which was of great advantage for unipolar pacing in the present case.…”
Section: Discussionmentioning
confidence: 42%
“…We advanced the guide-wire into the area of the old myocardial infarction for pace-mapping; therefore, the pacing threshold at the area was high. Previous reports showed that unipolar pacing threshold was lower compared with the bipolar pacing threshold [10], which was of great advantage for unipolar pacing in the present case.…”
Section: Discussionmentioning
confidence: 42%
“…Some studies investigated bipolar and unipolar leads pacing characteristics in the short-term, implying that the bipolar group had fewer sensing and pacing failure. 10,11 The probable underlying mechanism has been declared to be related to the coaxial design of Medtronic bipolar leads, which result in a lower chance of stray signal pick up and better conduction performance. 10 Furthermore, the pacing threshold illustrated to be more stable regarding bipolar steroid-eluting leads in all chambers in the longterm.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The probable underlying mechanism has been declared to be related to the coaxial design of Medtronic bipolar leads, which result in a lower chance of stray signal pick up and better conduction performance. 10 Furthermore, the pacing threshold illustrated to be more stable regarding bipolar steroid-eluting leads in all chambers in the longterm. 2 Our finding also demonstrated that bipolar leads have better long-term pacing characteristics because of the significant rise observed in pacing threshold of unipolar leads in the right atrium and left ventricle but not regarding bipolar group and significantly greater pacing threshold of left ventricular unipolar leads at follow up.…”
Section: Discussionmentioning
confidence: 99%
“…We illustrated that bipolar steroid‐eluting epicardial leads remained functional significantly better than unipolar nonsteroid‐eluting ones. Some studies investigated bipolar and unipolar leads pacing characteristics in the short‐term, implying that the bipolar group had fewer sensing and pacing failure 10,11 . The probable underlying mechanism has been declared to be related to the coaxial design of Medtronic bipolar leads, which results in a lower chance of stray signal pick‐up and better conduction performance 10 .…”
Section: Discussionmentioning
confidence: 99%